Effective moisture diffusivity determination and mathematical modelling of drying curves of apple pomace - Kara, Cem; Doymaz, Ibrahim (SPRINGER, 2015)
Drying of apple pomace representing by-products from apple juice processing was studied. The results obtained show that moisture content of the pomace decreases with time and temperature. The Midilli et al. model was selected as the best mathematical model for describing the drying kinetics of the apple pomace. The effective moisture diffusivity varied from 1.73 x 10(-10) to 4.40 x 10(-10) m(2)/s and the activation energy was calculated to be 29.65 kJ/mol.
Keywords: AIR; PRETREATMENTS; KINETICS; PARAMETERS; BEHAVIOR; QUALITY; SLICES; LEAVES; SEEDS; Thermodynamics; Mechanics